Primary esophageal mucosa-associated lymphoid tissue lymphoma: A case report and review of literature. Issue 13 (March 2017) - Ma, Qiang; Zhang, Chun; Fang, San'gao; Zhong, Peng; Zhu, Xiangfeng; Lin, Li; Xiao, Hualiang
Abstract: Rationale: Mucosa-associated lymphoid tissue (MALT) lymphoma is a low grade malignant B cell lymphoma which occurs mainly in the organs having mucosal layer. Though gastrointestinal tract is the most commonly involved extranodal site, primary esophageal MALT lymphoma is very rare with less than 20 cases reported in literature. Patient concerns: A 75-year-old man was referred to our hospital for evaluation of dysphagia. Endoscopy revealed a submucosal tumor located in the middle and lower third of esophagus. CT chest and endoscopic ultrasound revealed a 15.5 × 5.9 × 4.0 cm well circumscribed submucosa esophageal tumor. Test for serum antibody against H. pylori was negative. Due to the large tumor size, patient underwent surgical resection. Histological examination showed a submucosal tumor consisting of multiple nodules of varying sizes with intact covering squamous epithelium. The nodules were mainly composed of diffusely and monoclonal proliferating centrocyte-like or monocyte-like cells. Follicular colonizations were observed without lymphoepithelial lesions. The tumor cells were diffusely positive for CD20, PAX-5, Bcl-2 and follicular dendritic cells were positive for CD21, CD23. Monoclonal gene rearrangement was positive for immunoglobulin heavy chain gene, Kappa light chain gene and Lambda light chain gene. Diagnoses: Based on these findings, final diagnosis of esophageal MALT lymphoma was made. Outcomes: At 8 month follow up, no recurrence or metastases was detected. Lessons: Esophageal MALT lymphoma is a rare disease with definitive diagnosis possible only after histopathological examination. It carries good prognosis due to low malignant potential.